Replacement of maize by sorghum in broiler chicken diet: A metaanalysis study of its effects on production performance, mineral tibia content, intestinal villi and nutrient digestibility - Hidayat, Cecep; Jayanegara, Anuraga; Adli, Danung Nur; Sadarman, Sadarman; Sholikin, Mohammad Miftakhus; Wahyono, Teguh; Herdiawan, Iwan; Brahmantiyo, Bram; Isbandi, Isbandi; Rusdiana, Supardi (Agriculture and Natural Resources, 2022)
Importance of the work: The demand for maize is increasing every year. Sorghum is well-known as a replacement feed for broiler chickens. Objectives: To evaluate the effect of dietary sorghum inclusion (by replacing maize) in a broiler chicken diet on the production performance, mineral calcium (Ca) and phosphorus (P) tibia content, intestinal villi and nutrient digestibility using a meta-analysis technique. Materials & Methods: The data originated from published scientific articles obtained using search engines (Scopus and Google Scholar). The next stage was the evaluation of suitability regarding the research topic and study objectives, after which 20 articles were selected for the database. The database was statistically analyzed using a mixed model, with the variable level of inclusion of sorghum in broiler chicken diets analyzed using a fixed effect, while the different experiments were analyzed using random effects. Results: The inclusion level of sorghum in the broiler chicken diet did not significantly affect the main parameters of broiler chicken performance—average daily gain, feed conversion ratio, mortality and average daily feed intake. The dietary sorghum level did not significantly affect villus height, crypt depth or the tibia mineral content (Ca and P). Furthermore, the dietary sorghum inclusion level did not significantly affect dry matter and fat digestibility. Main finding: Sorghum has a biological effect that is not different from maize, so sorghum is recommended to be used as an energy source in broiler feed.